PENYIDIKAN TINDAK PIDANA PERTAMBANGAN DI LUAR TITIK KOORDINAT WILAYAH IZIN USAHA PERTAMBANGAN PADA DIREKTORAT RESERSE KRIMINAL KHUSUS POLDA SUMBAR - Yose, Hendra (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Regarding Mineral and Coal Mining, the mining permit area is regulated in Article158 of Act Number 4 of 2009. West Sumatera Province, with its rich natural resources,attracts every person and corporation to carry out mining activities in various ways anduses of equipment that is not only traditional but also modern equipment using heavyequipment. The one of the modes of mining committed to carry out mining, theinvestigation was carried out by the Special Criminal Investigation Directorate of the WestSumatra Regional Police.